Analisis Sistem Informasi SI-AWAS di SMKN 8 Bandung: Analysis of the SI-AWAS Information System at SMKN 8 Bandung - Rafly Aditya; Muhammad Alfiansyah; Debi Irawan (STMIK PONTIANAK, 2026)
The SI-AWAS Information System is a face recognition-based student attendance innovation implemented at SMKN 8 Bandung to improve the accuracy of attendance records and the effectiveness of discipline supervision. Although designed to assist with school administrative processes, the implementation of this system still faces various constraints, such as limited user access, suboptimal data integration, and a digital literacy gap among teachers, staff, and students. This study aims to analyze the effectiveness and efficiency of SI-AWAS using the PIECES framework (Performance, Information, Economy, Control/Security, Efficiency, Service) thru a qualitative approach with a case study design. Data was obtained thru semi-structured interviews, observation, and document study, and then validated using source, technique, and time triangulation. The expected research results will include a comprehensive overview of system performance, the quality of information produced, the efficiency of the attendance process, the economic aspects of operation, data security levels, and the quality of system services for users. This analysis also aims to identify both technical and non-technical barriers and formulate recommendations for improvement for schools and system developers. This research contributes to enriching the literature on evaluating educational information systems, while also providing an empirical basis for improving the quality of SI-AWAS at SMKN 8 Bandung.